Rineloricaria isaaci (Loricariidae: Loricariinae), a new species of loricariid catfish from the Uruguay River basin - Rodriguez, Mónica (2008)
Rineloricaria isaaci is described from tributaries of the Uruguay River basin in Argentina, Brazil and Uruguay. The new species is distinguished by having a long and wide area of naked skin at the snout tip, surpassing the anteriormost pore of the infraorbital ramus of the sensory canal, approximately in the middle of the third postrostral plate, and by its particular sexual dimorphism characterized by the long pectoral and pelvic fins of mature males.